Demographic Context, Mass Deportation, and Latino Linked Fate. (November 2020) - Maltby, Elizabeth; Rocha, Rene R.; Jones, Bradford; Vannette, David L.
Abstract: What explains why some Latinos feel strongly tied to their coethnics while others do not? Demographic context is one of the most cited predictors of identity strength, but the size and direction of its effects are disputed. Geographic differences in policy environments may explain the phenomenon. We argue that high levels of immigration enforcement indirectly lead to increased feelings of ethnic linked fate by determining where and how demographic context—in this case, the size of the immigrant population—will be salient. To test this, we combine information from local immigration-enforcement data (obtained via Freedom of Information Act requests) with the Latino Decisions' 2016 Collaborative Multiracial Post-Election Survey. The results suggest native-born Latinos have a stronger sense of ethnic linked fate when they live near large immigrant populations and rates of enforcement are high. When enforcement is low, the presence of immigrants has a negligible effect on native-born attitudes. Foreign-born Latinos' sense of linked fate is unaffected by policy context. These results suggest that as immigration enforcement becomes intensifies, conservative politicians may see increased backlash, at least in certain communities, from native-born Latinos. This is because feelings about ethnic linked fate correlate with increased participation and more proimmigrant policy stances.